Prosecutorial Vindictiveness in the Criminal Appellate Process: Due Process Protection After United States v. Goodwin - Michigan Law Review (1982)
This Note reformulates the doctrine of prosecutorial vindictiveness in light of the distinction drawn in Goodwin between pretrial and posttrial charging decisions. Part I recounts the development of the vindictiveness concept, and argues that in extending the doctrine beyond the factual settings which moved the Supreme Court to fashion its original prophylactic rule, the circuit courts have seriously eroded an essential due process safeguard. Part II critically examines the distinction between pretrial and posttrial charging decisions relied upon in Goodwin. Developing the logical corollary of the Goodwin holding, this Part argues that just as the pretrial situation does not warrant an inflexible presumption of vindictiveness when prosecutors substitute more serious charges, such a presumption is fully warranted after an initial trial. During this posttrial period, defendants' interests reach their apex and the government's interest in more serious charges significantly declines. Part III sets forth a revitalized prophylactic rule which reflects this balance, and responds to the possible objections to such an approach